Experimental design for evaluating the effect of lighting interventions on patients with Alzheimer's: A review: Dementia care research (research projects; nonpharmacological)/Therapeutic strategies and interventions. (7th December 2020) - Mathur, Pegah; Rider, Traci Rose; Place, Wayne
Abstract: Background: Alzheimer's disease is expected to become a major public health problem in the U.S. for the aging population. It is projected that in 2050, 65% of the aging population will die of Alzheimer's. This raises the questions of whether and how we are prepared to provide care for this growing population. In this regard, the built environment can have a crucial role in supporting care and cure processes for the disease. Among the environmental variables that impact the provision of care for Alzheimer patients, lighting is especially consequential as it is known as a non‐invasive cure method that can stimulate the circadian rhythm and mitigate the issues of sleeping disturbance and agitation. Nevertheless, previous experimental research on this topic is inconclusive since many studies failed to present important variables and strategies used in their experimental designs (e.g. characteristics of the lighting device, exposing light intensity and spectral quantity, time‐series design and frequency of the interventions, the amount of light entered into the subject's eyes). Method: This paper reviews the existing research on lighting and Alzheimer's to develop a framework that gives structure to the design of experimental research on the effect of lighting interventions on Alzheimer's patients (e.g. variables, contextual factors, control strategies). Result: This framework can facilitate future research on this topic as it enables the researchers to improve the internal validity of their results by improving their research design. Furthermore, this proposed framework can lead to a consistency in defining and using variables, control factors, and applicable findings across different studies to facilitate replication of experimental studies and inform the researcher on the generalizability of the findings. Conclusion: Furthermore, this proposed framework can lead to a consistency in defining and using variables, control factors, and applicable findings across different studies to facilitate replication of experimental studies and inform the researcher on the generalizability of the findings.